2020
DOI: 10.17159/2411-9717/1146/2020
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of whole-body vibration exposure of mining truck drivers

Abstract: SYNOPSIS Whole-body vibration (WBV) exposure measurements taken from 105 truck drivers employed in 19 mines and other workplaces were evaluated with the criteria prescribed in EU 2002/44/EC directive, BS 6841 (1987), ISO 2631-1 (1997). and ISO 2631-5 (2004) standards. The highest vibration acceleration was measured on the vertical Z-axis. The highest WBV exposure occurred in the RETURN, HAUL, and SPOT phases while the lowest exposure took place in the LOAD and WAIT phases. Crest factors on all axes were gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As mentioned in section 2.3, equation ( 13) can be used in cases where there are several investments during the life of the project. In [31], such cases are referred to as non-conventional cashflows. The NPV is not appropriate for evaluating investment projects with non-conventional cashflows [31], [32].…”
Section: Applications Of the Npv Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in section 2.3, equation ( 13) can be used in cases where there are several investments during the life of the project. In [31], such cases are referred to as non-conventional cashflows. The NPV is not appropriate for evaluating investment projects with non-conventional cashflows [31], [32].…”
Section: Applications Of the Npv Methodsmentioning
confidence: 99%
“…In [31], such cases are referred to as non-conventional cashflows. The NPV is not appropriate for evaluating investment projects with non-conventional cashflows [31], [32]. However, equation (6) shows that the SCRO method can evaluate such projects.…”
Section: Applications Of the Npv Methodsmentioning
confidence: 99%
“…An example is the research described in the article by Tekin regarding operators of internal combustion machines in Turkey in the field of WBV (whole-body vibration) [16]. Similarly, the article by Erdem et al describes WBV observed in haul truck operators [17]. The topic of noise generated by various devices, including underground mining machines, both diesel and electric, has been raised in an article on mining processing machines [18].…”
Section: State Of the Artmentioning
confidence: 99%